The Relationship between Price Bundling, Brand Image and Purchasing Decisions on Shopee Indonesia E-Commerce - Aref Puadi; Meitiana; Vivy Kristinae (Jurnal Manajemen Sains dan Organisasi, 2023)
Objective - This research aims to determine the influence of brand image on purchasing decisions and price bundling, both directly and indirectly, where price bundling is an intervening variable. Design/Methodology/Approach - This type of research is explanatory research with a quantitative approach. The population and sample in this research were students of SMA Muhammadiyah 1 Palangka Raya who had used Shopee e-commerce at least 3 times. The number of respondents in this study was 70 people. Analysis uses Partial Least Square (PLS), with the SmartPLS 3.0 analysis tool. Research findings - The results of this research show that brand image influences price bundling and purchasing decisions. Price bundling influences purchasing decisions. Price bundling mediates the influence of brand image on purchasing decisions. Conclusions and Implications – Brand image has a positive effect on purchasing decisions. Price bundling can positively mediate the relationship between brand image and purchasing decisions. Shopee can increase the role of price bundling and brand image to increase Shopee e-commerce users, especially for students at SMA Muhammadiyah 1 Palangka Raya.